Reflection of novice teachers on their teaching practice. Issue 4 (4th July 2022) - Lefebvre, Julie; Lefebvre, Hélène; Lefebvre, Bernard
ABSTRACT: This article focuses on novice teachers in Quebec colleges and vocational schools (CEGEPs) who often receive little support for their professional integration due to an almost complete lack of support programs. While novice teachers have professional experience in their fields of expertise, most have no training in pedagogy. Reflective practice is identified as a way to improve the novice's teaching practice. In order to better understand the pedagogical concept of reflection on action, six novice teachers engaged with a reflective toolkit in a qualitative, interpretive and exploratory study. The purpose of the study was to identify the categories of reflection called upon when novices reflected on their actions through use of tools in the proposed toolkit. The results show that the novice teachers developed a better understanding of the reflective process, particularly in the descriptive, discriminate and affective categories of reflection, and that they preferred video-based tools over those based on writing.